2012
DOI: 10.1063/1.4726157
|View full text |Cite
|
Sign up to set email alerts
|

The role of Cu-O bond length fluctuations in the high temperature superconductivity mechanism

Abstract: High critical current density and its field dependence in mixed rare earth (Nd,Eu,Gd)Ba 2 Cu 3 O 7−δ thin filmsWe review three different kinds of experiments that emphasize the non-BCS, inhomogeneous aspects of superconductivity in the high Tc cuprates. The first is the existence of two different energy scales in the superconducting state, initially identified by a comparison between tunneling and Andreev-Saint-James spectroscopies [Deutscher, Nature (London) 397, 410 (1999)]. The second are EXAFS measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Extensive researches by Llordés et al 63. and Deutscher64 have showed a similar result that the nanoscale strain present in ɛ zz map is responsible for a strong enhancement of pinning force for H // c . In the irradiated FST film, the nanoscale strain observed in ɛ xx map can lead to the extremely high F p,max and the shift of the F p,max to high field for H // ab .…”
Section: Resultsmentioning
confidence: 64%
“…Extensive researches by Llordés et al 63. and Deutscher64 have showed a similar result that the nanoscale strain present in ɛ zz map is responsible for a strong enhancement of pinning force for H // c . In the irradiated FST film, the nanoscale strain observed in ɛ xx map can lead to the extremely high F p,max and the shift of the F p,max to high field for H // ab .…”
Section: Resultsmentioning
confidence: 64%
“…However, oxygenation at low temperatures would be interesting because one can further modify the oxygen content of the YBCO films. [73][74][75][76] To overcome the low temperature limitation in the oxygenation of functional oxides, it has been shown that silver can be used as a catalyst to enhance the rate of oxygen incorporation. The use of silver as a catalyst for selective oxidation processes is well-known in different fields, especially in the hydrocarbon industry.…”
Section: View Article Onlinementioning
confidence: 99%
“…The in-situ nanocomposite CSD approach has also been widely investigated in recent years and much progress has been made in controlling the nanostructure and in understanding their physical properties [31][32][33]. For instance, a thorough analysis of the correlation between nanostrain generated within the YBCO matrix and the pinning force, evidenced that a novel vortex pinning mechanism may become effective in high temperature superconductors (HTS), which is closely associated to local disruption of the superconducting order parameter by tensile strain [30,34]. On the other hand, the comprehension of the complex growth mechanisms, involving kinetic and thermodynamic effects, forced to use multi-step processing paths to achieve control of the separate nucleation and growth processes of the two crystalline phases forming the nanocomposite [31,32].…”
Section: Introductionmentioning
confidence: 99%